2008
DOI: 10.1111/j.1740-8261.2008.01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Magic Angle Effect in the Equine Deep Digital Flexor Tendon Using a Low‐field Magnetic Resonance System

Abstract: Three isolated equine limbs were imaged with a low-field magnetic resonance system with a vertical magnetic field. Each limb was scanned in multiple positions with mild variation of the angle between the magnetic field and the long axis of the limb. When the long axis of the limb was not perpendicular to the magnetic field, a linear hyperintense signal was present at the palmar aspect of one of the deep digital flexor tendon lobes, at the level of the navicular bone and collateral sesamoidean ligaments, in pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 7 publications
1
18
0
Order By: Relevance
“…Similar changes have been reported previously with a low field MR system used with horses under general anaesthesia (Spriet et al 2007;Spriet and McKnight 2009). The orientation of the magnetic field relative to the limb in those studies is equivalent to the equine standing MR system used in this study, which accounts for the similar changes observed with the 2 systems.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar changes have been reported previously with a low field MR system used with horses under general anaesthesia (Spriet et al 2007;Spriet and McKnight 2009). The orientation of the magnetic field relative to the limb in those studies is equivalent to the equine standing MR system used in this study, which accounts for the similar changes observed with the 2 systems.…”
Section: Discussionsupporting
confidence: 84%
“…Such changes in signal intensity have been recognised in MR imaging of the foot of horses under general anaesthesia, both with high field (Busoni and Snaps 2002) and low field (Spriet et al 2007;Spriet and McKnight 2009) MR systems. Standing equine MR systems have a configuration similar to recumbent low field MR systems, with the magnetic field perpendicular to the sagittal plane of the limb.…”
Section: Introductionmentioning
confidence: 98%
“…In the horse, a MAE has been described in the DDFT (Busoni and Snaps 2002; Dyson et al . 2003; Spriet and McKnight 2009; Spriet and Zwingenberger 2009), the oblique sesamoidean ligaments (Smith et al . 2008) and in the collateral ligaments of the distal interphalangeal joint (Spriet et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, this only holds when the cartilage is completely isotropically-oriented with respect to the B 0 field since otherwise the so-called magic-angle effect has also to be considered, i.e., the appearance of individual cartilage layers depends on the angle between the sample and the static B 0 field 107 . Very similar effects are also observed when bone and tendon 108 samples are investigated in dependence on the orientation of the sample with respect to the magnetic field.…”
Section: Methods Of In Vitro Ecm Characterizationmentioning
confidence: 99%